The Charm School - DeMille, Nelson (London Grafton Books, 1988)
On a dark road deep inside the Russian woods at Borodino, a young American tourist picks up an unusual passenger with an explosive secret: an U.S. POW on the run from "The Charm School," a sinister operation where American POWs teach young KBG agents how to be model U.S. citizens. Their goal? To infiltrate the United States undetected. With this horrifying conspiracy revealed, the CIA sets an investigation in motion, and three Americans--an Air Force officer, an embassy liaison, a CIA chief--pit themselves against the country's enemies in a high-powered game of international intrigue.
Keywords: Soviet Union -- Etiquette for Children and Teenagers